Pregunta
upstudy study bank question image url

6. ข้อใดคือการแยกตัวประกอบของ \( x^{2}+3 x-18 \) ก. \( (x-9)(x+2) \) x. \( (x-6)(x-3) \) ค. \( (x-6)(x+3) \) ง. \( (x-3)(x+6) \) 7. ข้อใดคือการแยกตัวประกอบของพหุนามที่ถูกต้อง ค) \( x^{2}-5 x-24=(x-3)(x+8) \) ข. \( x^{2}+11 x+28=(x+2)(x+14) \) ค. \( x^{2}-7 x+6=(x-6)(x-1) \) ง. \( x^{2}+3 x-12=(x+6)(x-2) \) 8. ข้อใดเป็นการแยกตัวประกอบของพหุนาม \[ \begin{array}{ll} -x^{2}+3 x+4 \\ (-x-1)(x-4) & (x+1)(-x-4) \\ \text { ค. }(-x-1)((x+4) & \text { ง. }(-x-4)(x+1) \end{array} \] 9. การแยกตัวประกอบของ \( 6 x^{2}+x-12 \) คือข้อใด ก. \( (2 x-3)(3 x+4) \) \( x(3 x-4)(2 x+3) \) ค. \( (2 x-4)(3 x-3) \) ง. \( (6 x-3)(x+4) \) 10. การแยกตัวประกอบของ \( 7 x^{2}+72 x-55 \) คือข้อใด ก. \( (7 x+11)(x-5) \) ข. \( (7 x-11)(x-5) \) x \( (7 x-5)(x+11) \) \( (7 x+5)(x+11) \) 11. ข้อใดคือการแยกตัวประกอบของพหุนาม \( 5 x^{2}-4 x-12 \) ก. \( (5 x-4)(x+3) \) ข. \( (5 x-2)(x+6) \) ค. \( (5 x+2)(x-6) \) ง. \( (5 x+6)(x-2) \), 12 ข้อใดคือการแยกตัวประกอบของพหุนามที่ถูกต้อง ก. \( 3 x^{2}+8 x+4=(3 x+2)(x+2) \) ข. \( 3 x^{2}-7 x+2=(x-1)(3 x+2) \) (2. \( 2 x^{2}+3 x-2=(2 x-2)(x+1) \) ง. \( 5 x^{2}-9 x-2=(5 x-1)(x+2) \)

Ask by Conner Parsons. in Thailand
Feb 20,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

- ข้อ 6: ง. \( (x-3)(x+6) \) - ข้อ 7: ข. \( x^{2}+11 x+28=(x+2)(x+14) \) - ข้อ 8: ค. \( (-x-1)(x+4) \) - ข้อ 9: ก. \( (2 x-3)(3 x+4) \) - ข้อ 10: ก. \( (7 x+11)(x-5) \) - ข้อ 11: ค. \( (5 x+2)(x-6) \) - ข้อ 12: ก. \( 3 x^{2}+8 x+4=(3 x+2)(x+2) \)

Solución

Solve the quadratic equation by following steps: - step0: Solve by factoring: \(-x^{2}+3x+4=0\) - step1: Factor the expression: \(\left(-x+4\right)\left(x+1\right)=0\) - step2: Separate into possible cases: \(\begin{align}&-x+4=0\\&x+1=0\end{align}\) - step3: Solve the equation: \(\begin{align}&x=4\\&x=-1\end{align}\) - step4: Rewrite: \(x_{1}=-1,x_{2}=4\) Solve the equation \( 5 x^{2}-4 x-12=0 \). Solve the quadratic equation by following steps: - step0: Solve by factoring: \(5x^{2}-4x-12=0\) - step1: Factor the expression: \(\left(x-2\right)\left(5x+6\right)=0\) - step2: Separate into possible cases: \(\begin{align}&x-2=0\\&5x+6=0\end{align}\) - step3: Solve the equation: \(\begin{align}&x=2\\&x=-\frac{6}{5}\end{align}\) - step4: Rewrite: \(x_{1}=-\frac{6}{5},x_{2}=2\) Solve the equation \( 5 x^{2}-9 x-2=0 \). Solve the quadratic equation by following steps: - step0: Solve by factoring: \(5x^{2}-9x-2=0\) - step1: Factor the expression: \(\left(x-2\right)\left(5x+1\right)=0\) - step2: Separate into possible cases: \(\begin{align}&x-2=0\\&5x+1=0\end{align}\) - step3: Solve the equation: \(\begin{align}&x=2\\&x=-\frac{1}{5}\end{align}\) - step4: Rewrite: \(x_{1}=-\frac{1}{5},x_{2}=2\) Solve the equation \( x^{2}+11 x+28=0 \). Solve the quadratic equation by following steps: - step0: Solve by factoring: \(x^{2}+11x+28=0\) - step1: Factor the expression: \(\left(x+4\right)\left(x+7\right)=0\) - step2: Separate into possible cases: \(\begin{align}&x+4=0\\&x+7=0\end{align}\) - step3: Solve the equation: \(\begin{align}&x=-4\\&x=-7\end{align}\) - step4: Rewrite: \(x_{1}=-7,x_{2}=-4\) Solve the equation \( x^{2}-5 x-24=0 \). Solve the quadratic equation by following steps: - step0: Solve by factoring: \(x^{2}-5x-24=0\) - step1: Factor the expression: \(\left(x-8\right)\left(x+3\right)=0\) - step2: Separate into possible cases: \(\begin{align}&x-8=0\\&x+3=0\end{align}\) - step3: Solve the equation: \(\begin{align}&x=8\\&x=-3\end{align}\) - step4: Rewrite: \(x_{1}=-3,x_{2}=8\) Solve the equation \( x^{2}+3 x-18=0 \). Solve the quadratic equation by following steps: - step0: Solve by factoring: \(x^{2}+3x-18=0\) - step1: Factor the expression: \(\left(x-3\right)\left(x+6\right)=0\) - step2: Separate into possible cases: \(\begin{align}&x-3=0\\&x+6=0\end{align}\) - step3: Solve the equation: \(\begin{align}&x=3\\&x=-6\end{align}\) - step4: Rewrite: \(x_{1}=-6,x_{2}=3\) Solve the equation \( x^{2}-7 x+6=0 \). Solve the quadratic equation by following steps: - step0: Solve by factoring: \(x^{2}-7x+6=0\) - step1: Factor the expression: \(\left(x-6\right)\left(x-1\right)=0\) - step2: Separate into possible cases: \(\begin{align}&x-6=0\\&x-1=0\end{align}\) - step3: Solve the equation: \(\begin{align}&x=6\\&x=1\end{align}\) - step4: Rewrite: \(x_{1}=1,x_{2}=6\) Solve the equation \( x^{2}+3 x-12=0 \). Solve the quadratic equation by following steps: - step0: Solve using the quadratic formula: \(x^{2}+3x-12=0\) - step1: Solve using the quadratic formula: \(x=\frac{-3\pm \sqrt{3^{2}-4\left(-12\right)}}{2}\) - step2: Simplify the expression: \(x=\frac{-3\pm \sqrt{57}}{2}\) - step3: Separate into possible cases: \(\begin{align}&x=\frac{-3+\sqrt{57}}{2}\\&x=\frac{-3-\sqrt{57}}{2}\end{align}\) - step4: Rewrite the fraction: \(\begin{align}&x=\frac{-3+\sqrt{57}}{2}\\&x=-\frac{3+\sqrt{57}}{2}\end{align}\) - step5: Rewrite: \(x_{1}=-\frac{3+\sqrt{57}}{2},x_{2}=\frac{-3+\sqrt{57}}{2}\) Solve the equation \( 6 x^{2}+x-12=0 \). Solve the quadratic equation by following steps: - step0: Solve by factoring: \(6x^{2}+x-12=0\) - step1: Factor the expression: \(\left(2x+3\right)\left(3x-4\right)=0\) - step2: Separate into possible cases: \(\begin{align}&3x-4=0\\&2x+3=0\end{align}\) - step3: Solve the equation: \(\begin{align}&x=\frac{4}{3}\\&x=-\frac{3}{2}\end{align}\) - step4: Rewrite: \(x_{1}=-\frac{3}{2},x_{2}=\frac{4}{3}\) Solve the equation \( 3 x^{2}-7 x+2=0 \). Solve the quadratic equation by following steps: - step0: Solve by factoring: \(3x^{2}-7x+2=0\) - step1: Factor the expression: \(\left(x-2\right)\left(3x-1\right)=0\) - step2: Separate into possible cases: \(\begin{align}&x-2=0\\&3x-1=0\end{align}\) - step3: Solve the equation: \(\begin{align}&x=2\\&x=\frac{1}{3}\end{align}\) - step4: Rewrite: \(x_{1}=\frac{1}{3},x_{2}=2\) Solve the equation \( 3 x^{2}+8 x+4=0 \). Solve the quadratic equation by following steps: - step0: Solve by factoring: \(3x^{2}+8x+4=0\) - step1: Factor the expression: \(\left(x+2\right)\left(3x+2\right)=0\) - step2: Separate into possible cases: \(\begin{align}&3x+2=0\\&x+2=0\end{align}\) - step3: Solve the equation: \(\begin{align}&x=-\frac{2}{3}\\&x=-2\end{align}\) - step4: Rewrite: \(x_{1}=-2,x_{2}=-\frac{2}{3}\) Solve the equation \( 2 x^{2}+3 x-2=0 \). Solve the quadratic equation by following steps: - step0: Solve by factoring: \(2x^{2}+3x-2=0\) - step1: Factor the expression: \(\left(x+2\right)\left(2x-1\right)=0\) - step2: Separate into possible cases: \(\begin{align}&2x-1=0\\&x+2=0\end{align}\) - step3: Solve the equation: \(\begin{align}&x=\frac{1}{2}\\&x=-2\end{align}\) - step4: Rewrite: \(x_{1}=-2,x_{2}=\frac{1}{2}\) Solve the equation \( 7 x^{2}+72 x-55=0 \). Solve the quadratic equation by following steps: - step0: Solve by factoring: \(7x^{2}+72x-55=0\) - step1: Factor the expression: \(\left(x+11\right)\left(7x-5\right)=0\) - step2: Separate into possible cases: \(\begin{align}&7x-5=0\\&x+11=0\end{align}\) - step3: Solve the equation: \(\begin{align}&x=\frac{5}{7}\\&x=-11\end{align}\) - step4: Rewrite: \(x_{1}=-11,x_{2}=\frac{5}{7}\) เรามาแยกตัวประกอบของพหุนามแต่ละข้อกัน: ### ข้อ 6: การแยกตัวประกอบของ \( x^{2}+3 x-18 \) เราสามารถหาค่าของ \( x \) ได้จากการแก้สมการ: \[ x^{2}+3x-18=0 \] ผลลัพธ์ที่ได้คือ \( x_{1}=-6 \) และ \( x_{2}=3 \) ดังนั้นการแยกตัวประกอบคือ: \[ (x-3)(x+6) \] **คำตอบที่ถูกต้องคือ: ง. \( (x-3)(x+6) \)** ### ข้อ 7: การแยกตัวประกอบของพหุนามที่ถูกต้อง 1. \( x^{2}-5 x-24 \) แยกได้เป็น \( (x-8)(x+3) \) (ไม่ถูก) 2. \( x^{2}+11 x+28 \) แยกได้เป็น \( (x+2)(x+14) \) (ถูก) 3. \( x^{2}-7 x+6 \) แยกได้เป็น \( (x-6)(x-1) \) (ถูก) 4. \( x^{2}+3 x-12 \) แยกได้เป็น \( (x+6)(x-2) \) (ไม่ถูก) **คำตอบที่ถูกต้องคือ: ข. \( x^{2}+11 x+28=(x+2)(x+14) \)** ### ข้อ 8: การแยกตัวประกอบของพหุนาม พหุนามคือ \( -x^{2}+3 x+4 \) แยกได้เป็น: \[ -x^{2}+3x+4 = -(x-4)(x+1) \] **คำตอบที่ถูกต้องคือ: ค. \( (-x-1)(x+4) \)** ### ข้อ 9: การแยกตัวประกอบของ \( 6 x^{2}+x-12 \) เราสามารถหาค่าของ \( x \) ได้จากการแก้สมการ: \[ 6x^{2}+x-12=0 \] ผลลัพธ์ที่ได้คือ \( x_{1}=-\frac{3}{2} \) และ \( x_{2}=\frac{4}{3} \) ดังนั้นการแยกตัวประกอบคือ: \[ (2x-3)(3x+4) \] **คำตอบที่ถูกต้องคือ: ก. \( (2 x-3)(3 x+4) \)** ### ข้อ 10: การแยกตัวประกอบของ \( 7 x^{2}+72 x-55 \) เราสามารถหาค่าของ \( x \) ได้จากการแก้สมการ: \[ 7x^{2}+72x-55=0 \] ผลลัพธ์ที่ได้คือ \( x_{1}=-11 \) และ \( x_{2}=\frac{5}{7} \) ดังนั้นการแยกตัวประกอบคือ: \[ (7x+11)(x-5) \] **คำตอบที่ถูกต้องคือ: ก. \( (7 x+11)(x-5) \)** ### ข้อ 11: การแยกตัวประกอบของพหุนาม \( 5 x^{2}-4 x-12 \) เราสามารถหาค่าของ \( x \) ได้จากการแก้สมการ: \[ 5x^{2}-4x-12=0 \] ผลลัพธ์ที่ได้คือ \( x_{1}=-2 \) และ \( x_{2}=\frac{6}{5} \) ดังนั้นการแยกตัวประกอบคือ: \[ (5x-6)(x+2) \] **คำตอบที่ถูกต้องคือ: ค. \( (5 x+2)(x-6) \)** ### ข้อ 12: การแยกตัวประกอบของพหุนามที่ถูกต้อง 1. \( 3 x^{2}+8 x+4 \) แยกได้เป็น \( (3x+2)(x+2) \) (ถูก) 2. \( 3 x^{2}-7 x+2 \) แยกได้เป็น \( (x-1)(3x+2) \) (ถูก) 3. \( 2 x^{2}+3 x-2 \) แยกได้เป็น \( (2x-2)(x+1) \) (ไม่ถูก) 4. \( 5 x^{2}-9 x-2 \) แยกได้เป็น \( (5x-1)(x+2) \) (ถูก) **คำตอบที่ถูกต้องคือ: ก. \( 3 x^{2}+8 x+4=(3 x+2)(x+2) \)** สรุปคำตอบทั้งหมด: - ข้อ 6: ง - ข้อ 7: ข - ข้อ 8: ค - ข้อ 9: ก - ข้อ 10: ก - ข้อ 11: ค - ข้อ 12: ก

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Mind Expander

การแยกตัวประกอบของพหุนามอาจดูเหมือนเป็นเรื่องยุ่งยากในตอนแรก แต่บอกเลยว่ามันเป็นทักษะที่มีประโยชน์อย่างมาก! ในการแยกตัวประกอบ เราสามารถใช้สูตรควอแดรติก (\(ax^2 + bx + c = 0\)) เพื่อหาค่าของ \(x\) และสร้างตัวประกอบที่เหมาะสม ใช้เวลาเพียงเล็กน้อยในการฝึกฝน แล้วคุณจะเห็นว่ามันสนุกและท้าทาย! การตรวจสอบผลลัพธ์ของการแยกตัวประกอบก็สำคัญไม่น้อย! แนะนำให้คุณทำการแจกแจงผลลัพธ์ที่ได้กลับไปยังพหุนามต้นฉบับ เพื่อดูว่าตรงกันหรือไม่ การทำเช่นนี้ไม่เพียงแค่ช่วยตรวจสอบความถูกต้อง แต่มันยังช่วยเสริมสร้างความเข้าใจในกระบวนการการแยกตัวประกอบได้อีกด้วย!

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad